DIGITALIZATION IN UNIVERSITY EDUCATION: DIDACTIC ASPECTS - Mariia A. Abysova; Mariia H. Kravchuk; Oksana M. Hurniak (Інформаційні технології і засоби навчання)
Intensively developing digital technologies are transforming the basic processes studied by the didactics of higher education: ways of the teacher-student interrelated activity; the student and the knowledge, skills, and competencies intended to be learnt and gained; the teacher and the methodology of educational material. The learning goals set by the information society shift the focus from mastering the system of knowledge and developing professional skills to developing competencies, the formation of students’ readiness to design their own unique educational trajectories based on a competency-based approach. As higher education becomes more digitalized, there is a shift from coordinating teaching and learning activities to projecting, forming, and mastering individual educational plans. To meet the challenges of modern education, educators are expected to be able to comprehend changes impacting all of the components of didactic theory, including goals, content, forms, technologies, and learning tools. Digitalization processes lead to the dominance of infographic forms of presentation of educational material instead of narrative (text) forms associated with the development of voluminous texts. The variety of forms of organization of educational activities in the digital educational environment is increasing significantly, they are becoming a dynamic open system of educational modules. The educators are being faced with new theoretical tasks due to the active modernization of university educational practice, including the need to find ways to implement continuity between traditional and innovative methods of organizing the educational process while taking into account specific cognitive, motivational, and need-based characteristics of the digital generation. The transition from teaching as the educators’ primary activity to the variety of pedagogical roles they play in the digital educational process actualizes teachers’ mastery of the information technologies and the development of their personal professional teaching strategy.